The Effectiveness of Helpdesk Services at the General Election Commission of Bengkulu Province in the Implementation of the 2024 Election - Anggraini, Fitri; Imanda, Antonio; Handayani, Tuti (Social Sciences Journal, 2025)
This study aims to examine the effectiveness of the Helpdesk Services provided by the General Election Commission (KPU) of Bengkulu Province in organizing the 2024 General Election. The primary focus is on the Helpdesk for Political Party Registration and Verification, which utilizes the SIPOL (Political Party Information System) application. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The study involved four informants: two key informants and two main informants, selected using purposive sampling. The theoretical framework used refers to Sedarmayanti (2009), which includes four indicators: input, production process, output, and productivity. The findings show that the input in the form of infrastructure and facilities was adequately provided and utilized. The production process followed established procedures, although some technical issues still require improvement. In terms of output, the helpdesk successfully delivered information in a timely, accurate, and transparent manner to election participants and the public. Regarding productivity, the helpdesk team was able to work efficiently and provide satisfaction to its users. Therefore, the Helpdesk Services of KPU Bengkulu Province in the 2024 General Election can be considered effective. This research is expected to contribute as an input for improving the quality of public services, especially in the context of digital-based electoral democracy.